1
$\begingroup$

There is "an important lemma" related to the Baker-Campbell-Haussdorff theorem which says that

$$ e^XYe^{-X} = Y + [X,Y] + \frac{1}{2!}[X,[X,Y]]+\ldots $$

Clearly if $[X,Y]=0$ we get (noting that $e^{-X}e^{X} = \mathbf{1}$) that

$$ e^X Y-Ye^X = [e^X,Y]=0 $$

Thus $[X,Y]=0$ implies $[e^X,Y]=0$. Is the converse of this true? If $[e^X,Y]=0$ then does that imply $[X,Y]=0$? By the above formula this would imply that if

$$ [X,Y] + \frac{1}{2!}[X,[X,Y]]+\ldots =0 $$

then $[X,Y]=0$. It is not immediately obvious to me why this might be the case.

$\endgroup$
2
$\begingroup$

If $[X,Y]=0$ all terms in your sum are zero, so it's no surprise that the sum is zero.

I will use the holomorphic functional calculus in a Banach algebra; this allows us to define $f(A)$ for any function $f$ holomorphic on an open domain that contains that contains the spectrum of the matrix $A$. There is probably a less technical way of doing this.

For $s\in[0,1]$, consider the function $f_s(z)=z^s$ (this requires choosing a branch for the logarithm, but that's no issue). Since the spectrum $\sigma(e^X)$ of $e^X$ is discrete, we can choose an domain $D$ with smooth boundary, $0\not\in D$, and $\sigma(e^X)\subset D$. Note that $$ f_s(e^X)=(f_s\circ\exp)(X)=e^{sX}, $$ since we have $f_s\circ\exp (z)=e^{sz}$. Then, since products are continuous, and integrals are limits of sums, $$ f_s(e^X)Y=\left(\frac1{2\pi i}\int_{\Gamma} f(z)\,(zI-e^X)^{-1}\,dz\right)Y =\left(\frac1{2\pi i}\int_{\Gamma} f(z)\,(zI-e^X)^{-1}Y\,dz\right) =Y\left(\frac1{2\pi i}\int_{\Gamma} f(z)\,(zI-e^X)^{-1}\,dz\right)=Yf_s(e^X). $$ (note that $(zI -e^X)Y=Y(z-e^X)$, so $(zI -e^X)^{-1}Y=Y(z-e^X)^{-1}$). So we have that $$ e^{sX}Y=Ye^{sX},\ \ s\in[0,1]. $$ Now differentiate both sides and evaluate at $s=0$, to get $$ XY=YX. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.